Microbial landscapes of the rhizosphere soils and roots of Luffa cylindrica plant associated with Meloidogyne incognita - Qu, Ling; Dai, Kang; Wang, Jie; Cao, Li; Rao, Zhongchen; Han, Richou (Frontiers in Microbiology, 2023)
The root-knot nematodes (RKN), especially Meloidogyne spp., are globally emerging harmful animals for many agricultural crops. To explore microbial agents for biological control of these nematodes, the microbial communities of the rhizosphere soils and roots of sponge gourd (Luffa cylindrica) infected and non-infected by M. incognita nematodes, were investigated using culture-dependent and -independent methods. 32 culturable bacterial and 8 fungal species, along with 10561 bacterial and 2427 fungal operational taxonomic units (OTUs), were identified. Nine culturable bacterial species, 955 bacterial and 701 fungal OTUs were shared in both four groups. More culturable bacterial and fungal isolates were detected from the uninfected soils and roots than from the infected soils and roots (except no fungi detected from the uninfected roots), and among all samples, 9 bacterial species (Arthrobacter sp., Bacillus sp., Burkholderia ambifaria, Enterobacteriaceae sp., Fictibacillus barbaricus, Microbacterium sp., Micrococcaceae sp., Rhizobiaceae sp., and Serratia sp.) were shared, with Arthrobacter sp. and Bacillus sp. being dominant. Pseudomonas nitroreducens was exclusively present in the infested soils, while Mammaliicoccus sciuri, Microbacterium azadirachtae, and Priestia sp., together with Mucor irregularis, Penicillium sp., P. commune, and Sordariomycetes sp. were found only in the uninfected soils. Cupriavidus metallidurans, Gordonia sp., Streptomyces viridobrunneus and Terribacillus sp. were only in the uninfected roots while Aspergillus sp. only in infected roots. After M. incognita infestation, 319 bacterial OTUs (such as Chryseobacterium) and 171 fungal OTUs (such as Spizellomyces) were increased in rhizosphere soils, while 181 bacterial OTUs (such as Pasteuria) and 166 fungal OTUs (such as Exophiala) rose their abundance in plant roots. Meanwhile, much more decreased bacterial or fungal OTUs were identified from rhizosphere soils rather than from plant roots, exhibiting the protective effects of host plant on endophytes. Among the detected bacterial isolates, Streptomyces sp. TR27 was discovered to exhibit nematocidal activity, and B. amyloliquefaciens, Bacillus sp. P35 and M. azadirachtae to show repellent potentials for the second stage M. incognita juveniles, which can be used to develop RKN bio-control agents. These findings provided insights into the interactions among root-knot nematodes, host plants and microorganisms, which will inspire explorations of novel nematicides.